Transformasi Loyalitas Primordial sebagai Basis Identifikasi Kepartaian: Kasus Partai Kebangkitan Bangsa dalam Pemilihan Umum 1999 dan 2004 - Suryadi, Karim Suryadi (Mediator, 2005)
Transformation of primordial loyalty into the political sphere rather than understanding of the substance of the party’s platform is a key factor for PKB’s (National Awakening Party) devotees to adhere to the party. The platform has not been effectively socialized. The practice of the party has not been believed as a requisite condition to create an order society. On the other hand, adhering to Nahdlatul Ulama (NU) and inclining to submit to orders or wishes of Kiai (Muslim Scholars) is believed among PKB’s voters as a means by which a good community is created(khoerul barriyah). Therefore, since the 2004 General Election, Kiai’s political communication and orientations have become the partisans’ primary roles among PKB’s constituents.